Mechanic: resurrection [videorecording (DVD)] - Gansel, Dennis, 1973-; Statham, Jason, 1967-; Alba, Jessica, 1981-; Jones, Tommy Lee, 1946-; Yeoh, Michelle, 1963- (Dreamscape horizon., 2016)
Arthur Bishop returns as the Mechanic in the sequel to the 2011 action thriller. When the deceitful actions of a cunning but beautiful woman force him to return to the life he left behind, Bishop's life is once again in danger as he has to complete an impossible list of assassinations of the most dangerous men in the world.